Automative Unwinding of Waste Paper from Reel Spools - Pavel Lehocky; Robert Kohar; Slavomir Hrcek; Jan Podhorsky; B. Surmova; Stefan Medvecky; Alena Hrcekova (Communications - Scientific letters of the University of Zilina, 2007)
Paper industry deals with procedures for conceptual and final design of a machine intended for unwinding paper that remains on reels during a certain phase of paper producing. Design procedure of the machine is a subject of this paper. The machine was designed as a mechatronic unit consisting of a mechanical part, an electric part and a pneumatic part. 3D CAD/CAM system Pro/ENGINEER was used for the design of the mechanical part. For the automation processes the PLC unit connected with the frequency changing unit and asynchronous drive were used as a central drive for the unwinding machine.